2004
DOI: 10.3928/01484834-20040101-06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spirituality Content in Nursing Textbooks

Abstract: Although most nurses believe spiritual care is an integral component of quality, holistic nursing care, they rarely address spiritual issues and typically feel unprepared to do so. One reason for nurses’ lack of preparedness to provide spiritual interventions is that their basic education only minimally discusses spirituality and related issues. This is compounded by the problem that only sporadic reference to spiritual care is found in most nursing textbooks. This study was conducted to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
0
39
0
3
Order By: Relevance
“…McEwen (2004) found that little nursing education centers on spirituality. Informing women that chaplains are available to them if they wish could be part of the care process.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…McEwen (2004) found that little nursing education centers on spirituality. Informing women that chaplains are available to them if they wish could be part of the care process.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Despite this competency requirement, international research continues to show that nurses perceive themselves as unsure of how to implement spiritual care in practice (Burkhart and Schmidt, 2012). Their uncertainty relates to a lack of a clear understanding of what spirituality means and what spiritual care entails (McEwen, 2004;McSherry, 2007;Smyth and Allen, 2011) and poor educational preparation (Milligan, 2004;Ozbasaran et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore inadequate educational preparation has left RNs unclear in how to implement competent spiritual care (McEwen, 2004(McEwen, , 2005McSherry and Jamieson, 2011). As a result nurses prefer to refer spiritual care to religious workers and chaplains than provide spiritual care themselves (Ross, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Many nursing education programs prepar ing nurses for licensure only mini mally address the spiritual dimension (McEwen, 2004;Pesut, 2008). Many nursing education programs prepar ing nurses for licensure only mini mally address the spiritual dimension (McEwen, 2004;Pesut, 2008).…”
Section: Parish Nursingmentioning
confidence: 99%
“…2006). As such, spiritual care is a major component of quality, holistic care (McEwen, 2004;Shelly & Miller, revised the specialty to reflect all faith traditions, changing the name to FCN. However, due to the lack of spiritual emphasis in many nursing education programs, many nurses infrequently address spiritual issues related to their feeling of inadequacy in spiritual care training.…”
mentioning
confidence: 99%